JUDICIAL PRECEDENT AS A SOURCE OF TAX LAW - K. A. Ponomareva (Правоприменение)
The subject. The article is devoted to analysis of the role of the judicial precedent in the system of sources of tax law.Aim. The aim of this paper is to analyze the essence of national and international judicial precedents in the area of tax law.Methodology. The author uses methods of theoretical analysis, particularly the theory of integrative legal consciousness, as well as legal methods, including formal legal method and methods of comparative law.Results, scope. The role of judicial precedent in the system of sources of modern tax law is con-sidered in the article. Although the precedent in the Russian Federation as a source of law is not formally recognized, but actually used, its role in tax law is very high. The judicial precedent can be confidently recognized as the source of the tax law of Russia. In this case, courts often take on not only the role of interpreters of law, but their decisions act as a legal doctrine.Conclusions. The author comes to the conclusion that the role of decisions of courts, especially the highest courts, is growing, up to giving them signs of a precedent interpretation.